Pengaruh Budaya Lokal terhadap Praktik Agama di Masyarakat : Menggunakan Sesajen sebagai Pembuka Pada Sahur Pertama Bulan Ramadhan di Kampung Sukamulya Lembang - Akbar Rijal; Astrina Azzahra; Muhammad Nashir Marzuqi; Raissa Rahma Edita (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study examines the influence of local culture on religious practices in Sukamulya Village, Lembang, focusing on the use of ritual offerings during the first suhoor of Ramadan. Using a qualitative descriptive approach, data was collected through in-depth interviews with three key informants and direct observation of community practices. The findings reveal a complex interplay between local culture and religious practices, highlighting the need for community education to maintain Islamic principles while respecting cultural heritage. The study suggests that further research is needed to better understand the dynamics of cultural and religious acculturation in Indonesia.